Tanguar Haor, a diversified freshwater wetland - Kabir, Md. Humayun, 1943-; Amin, Shahalam M. N. (Shahalam Muhammad Nurul), 1951- (Dhaka : Academic Press and Publishers Library, 2007)
Study on freshwater wetlands in northeastern region of Bangladesh.
"Local people 's dependence on resources and participation in conservation practices."
Includes bibliographical references (p. 129-137).
Keywords: Wetlands -- Bangladesh